Changes over time in the risk of hospitalization for physical diseases among homeless men and women in Stockholm: A comparison of two cohorts. Issue 8 (December 2016) - Beijer, Ulla; Bruce, Daniel; Burström, Bo
Aims: To follow-up hospitalization for physical diseases among homeless men and women compared with a control group from the general population. The study also investigated the changes in the difference between the homeless men and women and the general population over time by comparing two cohorts of homeless people (2000–2002 and 1996). Methods: A total of 3887 people (24% women) who were homeless during the period 2000–2002 were compared with 11, 661 people from the general population with respect to hospitalization for physical diseases and injuries (2000–2010). Indirect comparisons were used to compare the relative risk (RR) of hospitalization between the cohort of people who were homeless in 2000–2002 with a cohort of those who were homeless in 1996. Results: Homeless people have an RR of being hospitalized for physical diseases twice that of the general population. The largest differences were found in skin diseases, infections, injury/poisoning and diseases of the respiratory system. Indirect comparison between people who were homeless in 2000–2002 and 1996 showed an increasing difference between young (18–35 years) homeless men and men in the control group (RR 1.32). The difference had also increased between homeless men and men in the control group for hospitalization for heart disease (RR 1.35), chronic obstructive pulmonary disease (RR 2.60) and poisoning (RR 1.89). Among women, the difference had decreased between homeless women and women in the control group for skin disease (RR 0.20) and injury/poisoning (RR 0.60). There was no significant difference between the sexes in the two homeless cohorts. Conclusions: There was no improvement in excess hospitalization among homeless people over time. The difference between young homeless men and young men in the general population increased between 1996 and 2000–2002.